2006
DOI: 10.1158/0008-5472.can-05-2494
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Represses Telomerase Activity via Both Transcriptional and Posttranslational Mechanisms in Human Prostate Cancer Cells

Abstract: Genistein, the most abundant isoflavone present in soybean has antiproliferative effects on a variety of cancer cells, including prostate cancer. However, the molecular mechanism of antiproliferative effects of genistein is not entirely understood. Because the activation of telomerase is crucial for cells to gain immortality and proliferation ability, we examined the role of genistein in the regulation of telomerase activity in prostate cancer cells. Here, we show that genisteininduced inhibition in cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 51 publications
4
59
0
1
Order By: Relevance
“…At the mechanistic level, β-catenin transcriptionally regulates the gene encoding Tert, which represents the enzymatic subunit of the telomerase enzyme (36). Furthermore, several natural compounds and their derivatives, as well as synthetic small molecules, achieve a potent inhibition of telomerase in cell culture models for epithelial cancers (37)(38)(39)(40). In this regard, the present colonic epithelial cell culture model differing in the expression of the tumor suppressor Apc gene, together with a model for Apc -/-drug-resistant telomerase-expressing colonic cancer stem cells, may provide novel mechanism-based experimental approaches for the identification of efficacious stem cell-targeted therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…At the mechanistic level, β-catenin transcriptionally regulates the gene encoding Tert, which represents the enzymatic subunit of the telomerase enzyme (36). Furthermore, several natural compounds and their derivatives, as well as synthetic small molecules, achieve a potent inhibition of telomerase in cell culture models for epithelial cancers (37)(38)(39)(40). In this regard, the present colonic epithelial cell culture model differing in the expression of the tumor suppressor Apc gene, together with a model for Apc -/-drug-resistant telomerase-expressing colonic cancer stem cells, may provide novel mechanism-based experimental approaches for the identification of efficacious stem cell-targeted therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein has been shown to suppress the proliferation of many types of cancer cell (Akiyama et al, 1987;Zwiller et al, 1991;Li and Sarkar, 2002;Jagadeesh et al, 2006;El Touny and Banerjee, 2007;Li et al, 2009). Although genistein was considered as a specific TPK inhibitor (Akiyama et al, 1987;Akiyama and Ogawara, 1991), additional evidence has been provided that genistein exerts multiple effects on cell growth including inhibition of neovascularization or angiogenesis (Fotsis et al, 1993), topoisomerase II (Okura et al, 1988), oncogene product activity (Zwiller et al, 1991), telomerase activity (Jagadeesh et al, 2006), Akt inhibition (Li and Sarkar, 2002;El Touny and Banerjee, 2007), and modulation of epigenetic events such as DNA methylation and/or histone acetylation (Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although genistein was considered as a specific TPK inhibitor (Akiyama et al, 1987;Akiyama and Ogawara, 1991), additional evidence has been provided that genistein exerts multiple effects on cell growth including inhibition of neovascularization or angiogenesis (Fotsis et al, 1993), topoisomerase II (Okura et al, 1988), oncogene product activity (Zwiller et al, 1991), telomerase activity (Jagadeesh et al, 2006), Akt inhibition (Li and Sarkar, 2002;El Touny and Banerjee, 2007), and modulation of epigenetic events such as DNA methylation and/or histone acetylation (Li et al, 2009). In this study, we demonstrated that genistein significantly induced a dose-dependent reduction of intracellular Ca 2Ăž in human umbilical CD105-positive MSCs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein inhibits the transcription of hTERT in breast MCF10AT benign cells and MCF7 cancer cells [62]. Genistein also decreases telomerase activity in prostate cancer cells [63,64]. Ouchi et al showed that the expression of hTERT and c-myc mRNA was downregulated by genistein in prostate cancer cells [63].…”
Section: Telomerase Activators and Pharmaceutical Importancementioning
confidence: 99%